The killer next door eaudiobook - Marwood, Alex (Tantor Media, 2014)
Everyone who lives at 23 Beulah Grove has a secret. If they didn't, they wouldn't be renting rooms in a dodgy old building for cash—no credit check, no lease. It's the kind of place you end up when you you've run out of other options. The six residents mostly keep to themselves, but one unbearably hot summer night, a terrible accident pushes them into an uneasy alliance. What they don't know is that one of them is a killer. He's already chosen his next victim, and he'll do anything to protect his secret.